(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
This article examines research outputs of several scientists on the shadow economy and makes some clarifications on the classification of it. The authors of this article think that with the help of accurate classification, the government can make correct decisions on controlling the shadow economy rate.